Physico-Chemical and Textural Changes in Elephant Foot Yam (Amorphophallus paeoniifolius) Tubers Infested by the Mealy Bug, Rhizoecus Amorphophalli Betrem during Storage - R S, Sreerag; C A, Jayaprakas; M S, Sajeev (Journal of Postharvest Technology, 2014)
Elephant foot yam, Amorphophallus paeoniifolius is an edible  aroid cultivated in the tropical countries. Corm or tuber is the  storage organ and is used as seed material or as a vegetable after  cooking. Owing to the indisputable palatability, cooking quality,  medical utility and therapeutic values of its tubers, this has been  dubbed as “King of tubers”. Infestation by the mealy bug,  Rhizoecus amorphophalli is a serious problem during its long term storage. This study aims at analysing the physicochemical  and textural changes in the mealy bug infested tubers of elephant  foot yam. For the study, infested and uninfested tubers were  stored for 4 months at ambient conditions and data on the  physico-chemical and textural changes were evaluated at monthly  interval. The moisture content showed a regular decreasing trend  in both uninfested and infested tubers registering higher loss for  infested set throughout the storage period. Starch and sugar  content decreased with storage period whereas fibre and ash  content increased. Functional properties of flours from the  uninfested tubers were low compared to the infested tubers and  these parameters slightly increased with storage period. Texture  profile analysis showed that the firmness of the infested tubers  were more than that of the uninfested tubers in their native form.
Keywords: Rhizoecus amorphophalli, Elephant foot yam; Tubers; Storage; Physico-chemical properties; Texture